Islamic Service, Branding, And Advertising Influence 212 Mart Co-Op Consumer Loyalty - Aslam Hanifa, Iqbal; Nuriyah, Aminah; Arofatul Marits, Shofi (Penerbit Goodwood, 2024)
Purpose: This thesis explores the impact of Islamic Service Quality, Islamic Branding, and Islamic Advertising on consumer loyalty within the 212 Mart Co-ops. Employing a quantitative approach, this study aimed to understand the dynamics of consumer loyalty in this context. Methodology/approach: Quantitative data were gathered through questionnaires, and Multiple Linear Regression was utilized for analysis. This study adopted a quantitative methodology supported by the SPSS program for data management and analysis. Results/findings: This study reveals the significant influences of Islamic Service Quality and Islamic Branding on consumer loyalty in the 212 Mart Co-ops. However, Islamic Advertising does not exhibit a notable impact on consumer loyalty. Interestingly, Islamic service quality and branding collectively exert a significant influence on consumer loyalty. Limitations: Acknowledging its boundaries, the study was confined to quantitative data, potentially influenced by biases in questionnaire responses. Additionally, the exclusion of other variables that impact consumer loyalty is recognized as a limitation. Contribution: This research makes a noteworthy contribution by emphasizing the considerable impact of Islamic Service Quality and Islamic Branding on consumer loyalty within the 212 March Co-op. This study provides valuable insights for marketers and policymakers, suggesting avenues to enhance these aspects for an overall improvement in consumer loyalty.aspects for an overall improvement in consumer loyalty.